Pengaruh model brain based learning terhadap kemampuan berpikir kritis matematis siswa kelas X SMAS Salafiyah Babussalam - Amelia, Mesy; Nurrahmawati; Afri, Lusi Eka (Karoteh Utama, 2023)
This research aims to determine the influence of the Brain Based Learning model on the mathematical critical thinking abilities of 10th-grade students at SMAS Salafiyah Babussalam. The type of research conducted here is a pre-experiment with an Intact-Group Comparison research design, where one class is divided into two groups. The sampling process employed random sampling techniques for selecting participants. Data on mathematical critical thinking abilities were collected through a test. Data analysis was carried out to test the hypotheses. Before hypothesis testing, a prerequisite test for normality was conducted. The results of the normality test indicated that the data did not follow a normal distribution. Therefore, hypothesis testing was conducted using the Mann Whitney test. The calculation results showed that the calculated z-score zscore > critical ztable, with a value of zscore = 4.39 > ztable = 1.96, leading to the rejection of the null hypothesis (H0). This means that there is a significant influence of the Brain Based Learning model on the mathematical critical thinking abilities of 10th-grade students at SMAS Salafiyah Babussalam. This research contributes significantly to the development of effective learning methods aimed at improving students' mathematical critical thinking abilities.